2016
DOI: 10.1109/tpwrs.2015.2449082
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Applicability of Uncertainty Importance Measures for Power System Studies

Abstract: This paper critically evaluates a number of uncertainty importance measures for use in power system stability studies. Sensitivity analysis of uncertain system parameters is vital as new technologies proliferate and the total level of system uncertainty grows. Accurate assessment of the importance of different uncertainties can guide power system operators towards parameters which will require the greatest levels of mitigation or increased monitoring in order to reduce the uncertainty and its subsequent impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…3(b). The Pearson correlation coefficient [10] is used to rank the importance of variables for case 2 and compared with Morris method. With the same number of simulations as Morris method, the Pearson approach generates the ranking of 1>3>2>5>8>7>6>4, i.e., similar but not exactly the same as Morris method.…”
Section: Sensitivity Analysis Through Morris Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3(b). The Pearson correlation coefficient [10] is used to rank the importance of variables for case 2 and compared with Morris method. With the same number of simulations as Morris method, the Pearson approach generates the ranking of 1>3>2>5>8>7>6>4, i.e., similar but not exactly the same as Morris method.…”
Section: Sensitivity Analysis Through Morris Methodsmentioning
confidence: 99%
“…In [8], nine SA techniques including probabilistic approaches have been compared in terms of their performance and efficiency, and it has been demonstrated that for many applications, the Morris screening approach is most suitable, providing a good balance between accuracy and efficiency. The Morris screening method has also been successfully applied in different areas [9] including the power system studies, where the focus has been on generator ranking, load classification and frequency support [10]. Morris screening approach is selected to perform sensitivity analysis in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity models are obtained through the simplified power flow model, which are effective for determining changes in power losses, nodal voltages, and other system states because of variations of nodal power injections. For the advantages of simplicity and accepted accuracy, sensitivity models have been applied in security‐constrained unit commitment, under‐frequency load shedding, and power system stability assessment …”
Section: Introductionmentioning
confidence: 99%
“…Due to spatial and temporal uncertainties associated with RES operation, in particular, it is neither practical nor feasible to perform TSA based on "worst case scenarios". Probabilistic methods are therefore used to assess various aspects of transient behaviour of power system with RES [12]- [18].…”
mentioning
confidence: 99%